Haplohyphes (Ephemeroptera: Leptohyphidae), new species and stage descriptions with a key to separate the species of the genus - Molineri, Carlos (Zootaxa, 2003)
Haplohyphes yanahuicsa sp. nov. from Bolivia, is described and illustrated from adult and nymphal stages, this constitutes the first report of the genus for that country. Imagos of both sexes of Haplohyphes aquilonius Lugo-Ortiz & McCafferty are described for the first time, and this species together with H. mithras (Traver) are recorded for the first time from Colombia. Haplohyphes furtiva Domínguez is proposed as a junior synonym of H. baritu Domínguez, and is also recorded for the first time from Bolivia. SEM photographs for the egg of H. baritu are presented, and compared with the eggs of other genera of the family. A key and illustrations to separate the six known species of the genus are given.